Lovastatin Analogues from the Soil-Derived Fungus Aspergillus sclerotiorum PSU-RSPG178 - Patima Phainuphong (2018)
© 2016 The American Chemical Society and American Society of Pharmacognosy. Three new lovastatin analogues (1, 4, and 5) together with four known lovastatin derivatives, namely, lovastatin (2), α,β-dehydrolovastatin (3), α,β-dehydrodihydromonacolin K (6), and α,β-dehydro-4a,5-dihydromonacolin L (7), were isolated from the soil-derived fungus Aspergillus sclerotiorum PSU-RSPG178. Their structures were established using spectroscopic evidence. Compound 5 exhibited the most potent activity against HMG-CoA reductase, with an IC50value of 387 μM. In addition, the present study indicated the direct interaction of compound 5 with HMG-CoA reductase. Compound 5 was considered to be noncytotoxic against noncancerous Vero cells, with an IC50value of 40.0 μM, whereas compound 2 displayed much stronger activity, with an IC50value of 2.2 μM.